(untitled) (Papeles, 2009)
This paper presents an overview of the research on the application of cognitive style theory to education. The study consists of three parts: first, the statement of the problem, in which the evolution and the sense given to the concept of “cognitive style” by the psycho-pedagogical research, is presented, second, theory and practice are contrasted with respect to specific educative and pedagogical issues and, finally, a reflection is made on how to face the problem of cognitive differences in educative and pedagogical settings.